Isolation Of Normal Buffalo Urinary Proteins - M. RAGA SUDHA; PARVATHALA KALYANI; VASILI ASHOK (International Journal of Pharma and Bio Sciences, 2012)
Uromodulin (85-90 kDa) and uroplakins (15-47 kDa) are normal urinary proteins produced by thick ascending limb of Henle’s loop of kidney tissue and urinary bladder respectively. Tissue specificity of these proteins facilitates the idea of transforming urinary system into a bioreactor. Identification of their promoter sequences helps in the construction of a transgene to express foreign proteins in the urine. High buffalo population and large volumes of urine voided by them, make them a better choice as model animals for transgenic research. The normal urinary proteins were precipitated by three precipitating agents viz., acetone, ammonium sulphate and sodium chloride. Analysis of protein precipitates by SDS PAGE revealed a prominent high molecular weight band at the level of 85 kDa in Coomassie stained gels. It is selectively precipitated by sodium chloride and it could be uromodulin. The inconsistent 50kDa band identified in acetone and ammonium sulphate precipitated samples in Coomassie stained gel and low molecular weight protein bands (27 kDa & 15 kDa) identified in silver nitrate stained gel could be uroplakins. The normal urinary protein precipitate concentrations with respect to the total urinary proteins were identified to be 1.1%, 0.156% and 0.2% for acetone, ammonium sulphate and sodium chloride precipitated samples respectively.